We’re less likely to collaborate in bad economic times - SIROLA, Nina (Institutional Knowledge at Singapore Management University, 2018)
In the fall of 1930, the U.S. economy was on a path to recovery following a contraction that occurred the year before. However, worries about the state of the economy, and the banking system in particular, prompted an increasing number of bank customers to attempt to withdraw their funds, an event known as a bank run. Because banks normally keep only a small proportion of deposits in cash, bank runs create a self-fulfilling prophecy such that initial concerns about banks’ possible insolvency ultimately cause insolvency. The bank run of 1930 resulted in the worst economic downturn in the modern history, the Great Depression.